Phytoplankton Communities and Cyanotoxin Production in Some Bulgarian Lowland Lakes and Reservoirs - Belkinova, Detelina; Teneva, Ivanka; Kazakov, Stefan; Stamenova, Silvia (Studia Ecologiae et Bioethicae, 2022)
One of the most evident consequences of eutrophication of waters is the progressive spreading of persistent cyanobacterial blooms. They are often accompanied by the production of cyanotoxins in concentrations, which are hazardous for human health. In this research, we analysed phytoplankton communities in four lowland water bodies, for the presence of cyanobacterial blooms and toxin production. The cyanobacterial biovolumes we found, determine three of the lowland water bodies: Onogur Reservoir (OR), Asparuhov Val Reservoir (AVR), and Srebarna Lake (SL) as “Alert Level 1” of potentially hazardous levels of cyanotoxins. Cyanobacterial biovolume exceeds the threshold value of 8 mm3 L-1 (recreational waters) in AVR and SL at the end of the summer period. In OR, we registered sustainable bloom of Microcystis spp. during the whole summer season, and extremely high average seasonal value of the total biovolume (146.5 mm3 L-1). Micro-cystins were reported in all four analysed water bodies, with the highest concentration in OR (6 µg L-1). Cylindrospermopsin was detected in AVR and OR, while saxitoxins were in AVR and SL. The concentrations of cyanotoxins do not exceed the guideline values in recreational waters. However, the increased biovolumes of cyanobacteria are a signal that in three of the analysed water bodies, monitoring is recommended at the levels of cyanotoxins during the summer period.